Impactos ambientais causados por efluentes industriais de abatedouros-frigoríficos de bovinos nos corpos hídricos - Braz, Lucas dos Santos. (Brasil, 2023)
The Brazilian cattle herd maintains its position as the second largest cattle herd in the world. Currently, the cattle trade is the most significant economic activity in Brazil, so this sector must comply with all health requirements, as well as paying attention to environmental issues. The practice of slaughtering cattle requires too much water, which, in almost all of it, is discarded as an industrial effluent with a high load of organic matter, such as blood, tissue fragments, among other wastes, which characterize a highly polluting waste. These wastewaters are classified as a factor of great environmental impact, since they cause deleterious changes in the surface and underground water bodies of the region where the slaughterhouse is located, when launched directly. In this context, it can be said that there is a growing awareness about wastewater treatment, and this is fundamental for the fight against water pollution and for the maintenance of public health. Thus, this work had the intention of carrying out a literature review about the environmental impacts that the effluents of slaughterhouses-slaughterhouses of cattle cause in the water bodies.